Redistribution and transmission mechanisms of income inequality - panel analysis of the affluent OECD countries - Josifidis Kosta; Dragutinović-Mitrović Radmila; Supić Novica; Glavaški Olgica (Panoeconomicus, 2016)
The aim of this paper is to point out the limitations of conventional approaches, articulated via political processes, in reducing income inequality. Using the panel data methods, on the sample of 21 affluent OECD countries in the period from 1980 to 2011, it is observed that the increase in labour productivity as well as preferences of voters to parties that advocate greater redistribution, contrary to common perception, not necessarily lead to reduction in income inequality. Increasing dominance of big capital in the field of technological progress changes the conventions about contribution of workers to labour productivity. The result is a weakening of workers’ bargaining power in relation to employers as well as increase in gap between labour productivity growth and real wage growth, which both lead to increase in income inequality. In comparison with the other political parties, it seems that the right-wing parties are more efficient in using voters’ support to implement their concept of the welfare state, which contributes to maintaining the high market-generated income inequality. Such situation could be explained that de jure power of the government depends on election results, whereas de facto power depends on the support of so-called globally-oriented super elites. [Projekat Ministarstva nauke Republike Srbije, br. 47010]